Semantic Involvement of Initial and Final Lexical Embeddings during Sense-Making: The Advantage of Starting Late - Van Alphen, Petra M.; Van Berkum, Jos J. (Frontiers in Psychology, 2012)
During spoken language interpretation, listeners rapidly relate the meaning of each individual word to what has been said before. However, spoken words often contain spurious other words, like day in daisy, or dean in sardine. Do listeners also relate the meaning of such unintended, spurious words to the prior context? We used ERPs to look for transient meaning-based N400 effects in sentences that were completely plausible at the level of words intended by the speaker, but contained an embedded word whose meaning clashed with the context. Although carrier words with an initial embedding (day in daisy) did not elicit an embedding-related N400 effect relative to matched control words without embedding, carrier words with a final embedding (dean in sardine) did elicit such an effect. Together with prior work from our lab and the results of a Shortlist B simulation, our findings suggest that listeners do semantically interpret embedded words, albeit not under all conditions. We explain the latter by assuming that the sense-making system adjusts its hypothesis for how to interpret the external input at every new syllable, in line with recent ideas of active sampling in perception.